Pengembangan Komik Digital Berbasis Canva dalam Pembelajaran Membaca Kelas IV Sekolah Dasar - Maulida Rizka Yulianti; Gusti Yarmi; Arita Marini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Low reading interest among elementary school students remains a major challenge in Indonesian language learning. Learning activities that rely primarily on textbooks and lecture-based instruction often reduce students' engagement and motivation to read. This study aimed to develop a Canva-Based Adventure Comic as a learning medium to improve the reading interest of fourth-grade students at SDN 01 Ciangsana. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, questionnaires, expert validation, and product trials involving students. The validation results indicated that the developed media was highly feasible, obtaining scores of 95% from the media expert, 98.3% from the material expert, and 98.4% from the language expert, with an overall average of 97.2%, categorized as very feasible. Student trials also produced highly positive responses, with feasibility scores of 96.7% in the one-to-one trial, 96.0% in the small-group trial, and 95.8% in the field test, resulting in an overall average of 96.1%, categorized as very feasible. The findings demonstrate that the Canva-Based Adventure Comic effectively presents learning materials through engaging illustrations, dialogues, and storylines, thereby increasing students' interest in reading while improving their comprehension of Indonesian language learning materials. Therefore, the developed learning media is considered highly feasible and effective for fostering reading interest among elementary school students.